Gut microbiota in gastric cancer: from pathogenesis to precision medicine - Huo, Shuang; Lv, Kaiying; Han, Lutuo; Zhao, Yu; Jiang, Jiakang (Frontiers in Microbiology, 2025)
Gastric cancer (GC) remains a significant global health burden, driven by a complex interplay of genetic, environmental, and microbial factors. Emerging evidence highlights the critical role of gut microbiota in gastric carcinogenesis, as microbial dysbiosis disrupts gastrointestinal homeostasis, fuels chronic inflammation, and promotes immunomodulation and metabolic reprogramming. Helicobacter pylori, a key microbial player, initiates tumorigenic pathways through reactive oxygen species production and the manipulation of dietary and microbial metabolites, leading to epigenetic and genetic alterations. Targeting gut microbiota has emerged as a promising therapeutic strategy, with interventions such as probiotics, prebiotics, dietary modifications, antibiotics, and fecal microbiota transplantation (FMT) showing potential in restoring microbial balance and attenuating tumor progression. Furthermore, advances in microbiota research have identified microbial biomarkers as valuable tools for early diagnosis, prognosis, and personalized treatment of GC. This review evaluates therapeutic strategies for microbiota modulation, assesses its diagnostic and prognostic potential, and highlights current gaps in the field. It also advocates for the integration of microbiota-targeted therapies into clinical practice, emphasizing their transformative potential in the prevention and management of GC. By addressing these aspects, this review aims to provide a comprehensive understanding of the role of gut microbiota in GC and to guide future research and clinical applications.